FINANCIAL PERFORMANCE AND FIRM SIZE ON FIRM VALUE IN THE HOSPITAL INDUSTRIES LISTED ON THE INDONESIA STOCK EXCHANGE (BEI) PERIOD 2020 - 2024 - Purwani Pujiati; Zainul Kisman (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
Firm value serves as a critical indicator for companies, investors, and policymakers in evaluating equity ownership. This study aims to analyze the partial effects of financial performance—comprising liquidity, profitability, activity, and solvency ratios—alongside firm size on the value of healthcare companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. A quantitative approach was employed using multiple linear regression analysis to test the hypotheses. The findings indicate that Current Ratio (CR), Return on Assets (ROA), and Total Asset (TA) have a significant partial effect on Price to Book Value (PBV), with significance values of 0.000, 0.000, and 0.001, respectively (p < 0.05). Conversely, Accounts Receivable Turnover (ART) and Solvency Ratio (SR) do not significantly influence firm value (p > 0.05). The R-squared value is 0.548, indicating that these variables contribute 54.8% to the variance in firm value, while the remaining 45.2% is influenced by other factors outside the scope of this study. These results suggest that market valuation in the healthcare sector is primarily driven by liquidity and profitability, whereas receivable management and solvency levels are less prioritized by investors in the post-pandemic era.